Load Flow and Transient Stability Analysis of the Gorontalo 150 kV Electrical System Post-Interconnection of the 10 MWp Isimu Solar Power Plant - Frengki Eka Putra Surusa; Ihksan Ihksan; Steven Humena; Sardi Salim (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2026)
The Isimu Solar Power Plant (PLTS) has been constructed for the Gorontalo power system. This plant is directly interconnected to the Isimu Substation bus via a 20 kV distribution line. This interconnection alters the system's power flow and impacts its stability. Consequently, an analysis of the main generation system's performance under steady-state conditions—considering system disturbances—was conducted for both pre- and post-interconnection scenarios. The Isimu PLTS interconnection improved the voltage profile at each substation bus by an average of 1.06% and resulted in minimal power losses of 0.43%, thereby enhancing overall system performance. During short-duration disturbances, the Gorontalo power system remained stable; following a disturbance, the generator rotor angle returned to normal operation one second faster than in the pre-interconnection state.